Population trends of ground-nesting birds indicate increasing environmental impacts from Eastern to Western Europe: different patterns for open-habitat and woodland species - Reif, Jiří; Koleček, Jaroslav; Morelli, Federico; Benedetti, Yanina (Frontiers in Environmental Science, 2023)
Introduction: Bird populations reflect the influence of major environmental changes, and the analysis of their long-term population trends concerning species-specific ecological traits can provide insight into biologically relevant impacts of such changes. In this respect, nest site is a particularly informative trait because ground-nesting bird species are more prone, in contrast to species nesting above the ground, to the impacts of nest predation which can be linked to various environmental drivers including the intensification of agriculture or woodland management. Here we hypothesize that a) ground-nesting species present negative trends due to environmental pressures mentioned above, b) such declining trends should be more pronounced in Western than in Eastern Europe because, in Western countries, the environmental threats are likely greater, and c) the interaction between nest site and habitat association will point at the habitat types where the presumed drivers most likely operate. Methods: We used population trends from 1980 to 2016 of 332 bird species in 16 European countries to test this hypothesis. Results: We found that the long-term population trends of ground-nesting birds are more negative than the trends of species nesting above the ground indicating the effect of nest predation, and this difference increased from Eastern to Western European countries, probably due to steeply increasing populations of nest predators in the West. However, the effect of longitude interacted with the habitat association being strong in woodland species and weak in open-habitat species. Discussion: This pattern suggests that the increased nest predation pressure in the West is linked to woodlands, probably due to higher abundances of mammalian herbivores that destroy forest ground and shrub layer, and thus leave the nests exposed to predators. In contrast, only a weak longitudinal pattern in open-habitat species indicates that the negative impacts of agricultural intensification are no longer confined to the Western part of the continent. Although nature conservation activities are generally successful in Europe, as indicated by benefits provided by the Natura 2000 network, our results uncovered substantial gaps in delivering such benefits.